Analysis of the reproductive status and stomach content of anurans in Agusan Marsh, Agusan del Sur - Molina, Joan D.
Reprodcution and dietary information.
Thesis Undergraduate (BS Biology)-U.P. Mindanao.
Keywords: Anurans; Diet composition; Reproductive status; Agusan Marsh; Agusan Marsh -- Agusan del Sur -- Mindanao, Philippines; Frogs; Toads; Anurans -- Habitat preferences; Anurans -- Reproduction; Anurans -- Conservation status and threats